2017
DOI: 10.1017/wet.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Preemergence and Postemergence Control of Artilleryweed (Pilea microphylla) in Container Nurseries and Landscapes

Abstract: These proceedings are a compilation of 14 papers that were presented at the regional meetings of the forest and conservation nursery associations in the United States in 2013. The Joint Northeast and Southern Forest Nursery Conference was held at the Holiday Inn City Centre, Lafayette, Indiana, July 22 to 25, 2013. Subject matter for the technical sections included nursery fertilization, black walnut research, and exploring the threat of hybrid Phytopthoras (and how to prevent this). Field trips included tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Pilea microphylla, commonly known as artillery weed, rockweed or gunpowder plant, is native to Mexico and tropical South America (Monro 2001). It is mainly utilized in gardens and landscapes as foliage or groundcover ornamental plant (Saha & al. 2017), but also for many ethnobotanical uses (Bhellum & Hamid 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Pilea microphylla, commonly known as artillery weed, rockweed or gunpowder plant, is native to Mexico and tropical South America (Monro 2001). It is mainly utilized in gardens and landscapes as foliage or groundcover ornamental plant (Saha & al. 2017), but also for many ethnobotanical uses (Bhellum & Hamid 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Once widely planted as an ornamental groundcover (Blessington and Collins, 1993), artillery weed spreads aggressively in landscape planting beds and in cracks in hardscapes. Saha et al (2017) reported that glyphosate provides only suppression of mature artillery weed, with fresh weight reductions ranging from 30% to 50% in one experiment. Numerous preemergence herbicides provide effective control, and herbicides including flumioxazin and glufosinate provide effective postemergence control (Saha et al, 2017).…”
Section: Natives Lacking Effective or Selective Management Optionsmentioning
confidence: 97%
“…Saha et al (2017) reported that glyphosate provides only suppression of mature artillery weed, with fresh weight reductions ranging from 30% to 50% in one experiment. Numerous preemergence herbicides provide effective control, and herbicides including flumioxazin and glufosinate provide effective postemergence control (Saha et al, 2017). Although many of these herbicides are available to homeowners, they are typically only available for purchase in very large quantities (e.g., 9.5-L bottles or 23-kg bags), which increases the cost considerably for homeowners managing small areas.…”
Section: Natives Lacking Effective or Selective Management Optionsmentioning
confidence: 97%
“…], large crabgrass [ Digitaria sanguinalis (L.) Scop. ], garden spurge ( Euphorbia hirta L.), and eclipta ( Eclipta prostrata L.) (Saha, Marble, Stewart, & Chandler, 2017; Saha et al., 2019). In turfgrass, FreeHand effectively controlled simazine (6‐chloro‐2‐ N ,4‐ N ‐diethyl‐1,3,5‐triazine‐2,4‐diamine)‐resistant ABG when applied preemergence in a zoysiagrass ( Zoysia spp.)…”
Section: Chemical Control Of Annual Bluegrassmentioning
confidence: 99%